A Knife Is Not a Pill Cutter (And Other Home Medication Safety Tips) - Kathleen E. Walsh; Michelle Bell; Caitlyn Allen (Patient Safety)
Children are more than twice as likely as adults to experience a medication error at home. Dr. Kathleen Walsh, pediatrician at Boston Children’s Hospital, discusses why that is the case and tips to keep kids (and anyone) safe.